The Effectiveness of Nutrition Counseling with Poster Media in Changing Knowledge about the Importance of Breakfast for Students in Timang Gajah Public Junior High Schools, Bener Meriah Regency - Natasya Muzakir; Andriani Andriani; Eva Fitriyaningsih; Rachmawati Rachmawati (Jurusan Gizi, Poltekkes Kemenkes Aceh, 2021)
Breakfast is an important eating and drinking activity before doing physical activities. People usually have breakfast at 06.00-09.00 A.M. Breakfast habits are strongly influenced by the level of knowledge. Nutrition knowledge can be increased through formal and informal education (counseling, training, seminars, and counseling) by using media as an attraction. Selecting the right media is expected to create interesting and effective message delivery. Good media are media that convey messages so that the target can know the content of the message and effectively change his behavior. This research employed a quantitative method with a quasi-experimental approach. This research was conducted in February 2021 at Timang Gajah Public Junior High Schools. The data were collected using a pretest-posttest with a control group design and a questionnaire, distributed to class VIII students in Timang Gajah Public Junior High Schools, Bener Meriah Regency. The research sample was 73 people. The data were analyzed using an independent t-test. This study has discovered an increase in knowledge about the importance of breakfast without using poster media with a p-value of 0.000. Meanwhile, counseling using poster media shows a significant increase with a p-value of 0.000. Using and not using poster media to increase students' knowledge about the importance of breakfast at Timang Gajah Public Junior High Schools, Bener Meriah Regency have a p-value of 0.000.